How Formal and Nonformal Education Shapes a Student: A Case of Minke from Pramoedya A. Toer’s Buru Tetralogy - FX Dono Sunardi; Pratiwi Retnaningdyah; Slamet Setiawan (IJORER : International Journal of Recent Educational Research, 2024)
Objective: The study aims to investigate the interplay between formal and non-formal education and their cumulative impact on the character development of Minke, a central figure in Pramoedya Ananta Toer’s Buru Tetralogy. Method: Drawing upon a comprehensive analysis of the tetralogy, the research meticulously examines Minke's educational experiences within and outside the institutionalized academic framework. By categorizing and evaluating his cognitive skills, linguistic proficiencies, and cultural identities acquired through formal education, juxtaposed with his extracurricular engagements and interactions outside the school, the study provided a nuanced portrayal of Minke's holistic learning journey. Results: The findings underscore the pivotal role of both formal and non-formal educational paradigms in shaping Minke's multifaceted persona. While formal education endows Minke with foundational skills and introduces him to European intellectual traditions, non-formal experiences enrich his character by exposing him to diverse societal challenges, fostering critical thinking, and nurturing a voice against colonial oppression. The synergistic integration of these educational modalities emerges as instrumental in molding Minke into a discerning, empathetic, and critically astute individual, distinctively depicted across the tetralogical narratives. Novelty: Contrary to prior singular emphases on formal or non-formal education, this research presents a holistic exploration that underscores the complementary nature of both educational realms in character development. The nuanced analysis provides fresh insights into the transformative potential of integrating diverse educational experiences, emphasizing their collective influence on individual and societal narratives as depicted in literary representations.